2019
DOI: 10.1039/c9py00547a
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional copolymerizability of o-phthalaldehyde in cationic copolymerization with vinyl monomers

Abstract: o-Phthalaldehyde is copolymerized via the unique active species, which allows the controlled copolymerization with alkyl vinyl ethers, alternating copolymerization, and copolymerization with sterically hindered nonhomopolymerizable vinyl monomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Therefore, depolymerization (unzipping) via the backbiting reaction at the oxonium chain end (Scheme D, left), which occurs below the equilibrium concentration of MDOP, was most likely suppressed when an ester bond with a CL unit exists next to the oxonium chain end (Scheme D, right). This result is partially similar to the copolymerization of nonhomopolymerizable monomers. …”
supporting
confidence: 68%
“…Therefore, depolymerization (unzipping) via the backbiting reaction at the oxonium chain end (Scheme D, left), which occurs below the equilibrium concentration of MDOP, was most likely suppressed when an ester bond with a CL unit exists next to the oxonium chain end (Scheme D, right). This result is partially similar to the copolymerization of nonhomopolymerizable monomers. …”
supporting
confidence: 68%
“…Based on previous work on the copolymerization of phthalaldehydes, the copolymerization of the allylated phthalaldehyde and unfunctionalized phthalaldehyde was investigated. [20,22,47] The allylated monomer was successfully incorporated in the copolymerization in a manner that allows variability in cross-linking density. It was found that a 1:1 equivalence of monomers was optimal for high incorporation rates (2.5:1 PPA:Allyl PPA) of the allylated monomer as well as the best overall yields of the statistical copolymer (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…EMPE, a β,β-dimethyl VE, was completely inert in the terpolymerization, probably due to steric hindrance (entry 10). Notably, the inefficiency of DHP and EMPE, which are small and nonhomopolymerizable, respectively, ,, is in sharp contrast to the alternating copolymerizations of these monomers with o -phthalaldehyde . Steric hindrance between these vinyl monomers and the MEK-derived carbocation is likely responsible for their inertness (Scheme C).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Notably, the inefficiency of DHP and EMPE, which are small and nonhomopolymerizable, respectively, 35,39,40 is in sharp contrast to the alternating copolymerizations of these monomers with o-phthalaldehyde. 41 Steric hindrance between these vinyl monomers and the MEK-derived carbocation is likely responsible for their inertness (Scheme 4C). From these results, VEs with appropriate reactivities were demonstrated to be important to both suppress VE homopropagation and generate polymers with sufficiently high MWs.…”
Section: Table 1 Cationic Terpolymerization Of Various Ves With Vcho ...mentioning
confidence: 99%